Factors Influencing the Effectiveness of Interventions: An Interaction of Instructional Set Size and Dose. Issue 4 (28th July 2020) - Hernandez-Nuhfer, M. Patricia; Poncy, Brian C.; Duhon, Gary; Solomon, Benjamin G.; Skinner, Christopher H.
Abstract: The current study examined digits correct per minute (DCPM) growth using explicit timing procedures across varying instructional set sizes (ISSs) and dose. Specifically, the study used a randomized group design to compare DCPM growth within three different ISSs (9, 18, and 36 multiplication facts) across three different levels of dose (2-, 4-, and 8-min sessions) over 24 intervention sessions. Data were analyzed using a multilevel piecewise model to determine whether there was a superior dose for each ISS to maximize DCPM growth and level changes. Significant findings showed an interaction effect of ISS and dose on growth slopes and final performance. As would be expected, the steepness of growth was dependent on ISS, with scores ranging from 1.30 DCPM (ISS 36, 2-min dose) to 4.68 DCPM/session (ISS 9, 8-min dose). Overall, an 8-min dose was superior, but this condition's relation to the other two doses appeared to interact with set size. Though researchers have identified evidence-based interventions (EBIs), few have evaluated how logistical factors such as ISS and dose interact with EBIs to affect learning. The current study provides preliminary recommendations for how to pair ISS and dose to guide intervention plans.